Estudo dos efeitos inotrópicos e toxicológicos de extratos da Tithonia diversifolia (Hemsl.) A. Gray em mamíferos - Lima, Adriana Karla de (2013)
Extracts from Tithonia diversifolia (TD) have been widely employed in Central and South America, Asia and Africa to help in the treatment of malaria, a disease to which millions of people are subjected in tropical countries. In spite of this, we were not able to find any scientific report dealing with their effects on the heart muscle functioning or describing their toxic effects. Such gaps are barriers for the TD derivatives to become a phytotherapic agent. Therefore, we have planned this study aiming to clarify the inotropic and toxicological effects of TD derivatives. Their effects on the muscle inotropism were investigated in isolated guinea pig atrium mounted in an organ chamber containing Tyrode solution oxygenated by carbogen mixture (5% CO2, 95% O2). The atria were stretched (1 gf) and stimulated at 2 Hz with suprathreshold electrical pulses. Their contractile forces were captured isommetrically and stored in computer to be analysed off line. The effect of AqF was determined after this fraction be added to the organ bath. The evaluation concerned to its effect on the L-type calcium current (ICa,L) was carried out in ventricular cardiomyocytes isolated according to the steps described by Shioya (2007). The intracellular calcium transients were also studied in these cells previously loaded with FLUO4-AM and monitored by confocal microscopy. The acute (ATx) and subacute (STx) toxicities of the crude extract of TD (CE) were evaluated in rats according to the steps proposed by OECD (2001a,b). Briefly: animals were separated by gender to create one control group and two treated groups. For the ATx study, the animals pertaining to the control group received orally only distilled water, whereas rats pertaining to the treated groups received, respectively, 2.5 g/kg and 5.0 g/kg of CE administered in a unique dose. The animals involved in the study were monitored for abnormal signals during 14 days. In the STx evaluation, the animals of the two treated groups received, respectively, 0.125 g/kg/day CE and 0.250 g/kg/day CE during 30 days. Animals were carefully observed for signals representing physiological and/or behavioral abnormalities. At the end of each toxicological protocol, the animals were anaesthetized for collecting blood and after that they were euthanized for the removal of organs. Our results showed that AqF depresses the atrial contractility in a dose-dependent fashion. However, concentrations greater than 2 g/l cause mechanical alternans , indicating that AqF can disturb the dynamics of the calcium release channels, which are present in the sarcoplasmic reticulum membrane. The effect of AqF on the L-type calcium current (ICa,L) was studied by recording how this fraction changes the inotropic effect produced by increasing concentrations of CaCl2. Our data showed that 2 g/l AqF increased the CaCl2 EC50 from 1.207 ± 0.139 to 2.846 ± 0.035 mM (n = 4, p < 0.05), suggesting that AqF is able to reduce ICa,L. Such conclusion was reinforced by testing the Bowditch phenomenon in atria incubated with 1.3 g/l AqF. In these experiments, AqF completely abolished the force overshoot , which is normally seen in the positive staircase Bowditch phenomenon. The depressant effect of AqF on the ICa,L was also supported by the decrease of intracellular fluorescence related to the subcellular calcium from 6.9 ± 0.4 (n = 53) to 5.3 ± 0.3 u.a. (n = 51; p < 0.05). In fact, direct measurements of ICa,L performed in patch clamped cardiomyocytes, confirmed the depressant effect of AqF on ICa,L. In these experiments, 80 g/ml of AqF reduced the density of ICa,L from 10.00 ± 1.22 to 7.80 ± 1.19 A/F (n = 4, p < 0.05). An expected consequence for the ICa,L reduction is the increase of the time required for the myocardial electrical wave to cross the atrioventricular node. Electrocardiograms from isolated guinea pig hearts confirmed the reduction of ICa,L because in the presence of AqF the heart presented a complete atrioventricular block (AVB). There was no involvement of potassium channels, neither the muscarinic nor the opioids receptors in the AqF myocardial depressant effect. We can conclude that the depressant effects of AqF in the myocardium contractility are due to a reduction of ICa,L. Studies concerned to the ATx and STx showed that the CE does not promote any signal of pain, abnormal behavior or mortality in the rats (DL50>5.0 g/kg). In STx, CE does not change water or food intakes, but in the animals treated with 0.250 g/kg/day a gain of weight occurred, suggesting water retention in the animal s body. Neutropenia, eosinopenia, lymphocytosis, and monocytosis were observed in treated animals during the ATx study. In animals pertaining to the STx study it was seen leucopenia, neutropenia, and monocytopenia. In ATx evaluation, the biochemical profile of the blood showed a reduction in the plasmatic urea but the aspartate and alanine aminotransferases, alkaline phosphatase, total and direct bilirubin, total protein, globulin, sodium, and uric acid increased. Similar results were found in the STx study, except for the urea that remained unchanged and for the glucose, creatinin, albumin, and potassium that presented an increase in their serum levels. These findings advise for precaution when TD derivatives were proposed as a therapeutic agent. We conclude that AqF reduces ICa,L leading to a negative inotropism and an AVB. The CE interferes with the hematopoietic system and promotes injuries for the liver and kidneys leading to a non-inflammatory tissue reaction.